1979
DOI: 10.1093/ptj/59.7.866
|View full text |Cite
|
Sign up to set email alerts
|

The “Fakeability” of the Attitudes Toward Disabled Persons Scale: Form B

Abstract: The purpose of this study was to provide evidence for or against the "fakeability" of the Attitudes Toward Disabled Persons Scale: Form B. Form B of the Scale was administered to 25 women, between the ages of 19 and 24, studying at a midwestern university. Seven days later, the subjects retook the test and were instructed to fake their answers so that they would receive a higher score. The difference between the true scores and the fake scores were not found to be significant, and it was concluded that the Att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although the ATDP Scale is the best known and most widely used scale to measure attitudes towards people with disabilities, concerns have been raised about its hypothesized unidimensional structure, outdated items, and its susceptibility to socially desirable responses (Antonak 1980, Livneh 1985, Cannon & Szuhay 1986, Yuker 1986, Antonak & Livneh 1988, Speakman et al. 1994).…”
Section: The Studymentioning
confidence: 99%
“…Although the ATDP Scale is the best known and most widely used scale to measure attitudes towards people with disabilities, concerns have been raised about its hypothesized unidimensional structure, outdated items, and its susceptibility to socially desirable responses (Antonak 1980, Livneh 1985, Cannon & Szuhay 1986, Yuker 1986, Antonak & Livneh 1988, Speakman et al. 1994).…”
Section: The Studymentioning
confidence: 99%
“…However, positive components in this study are also noted. Stewart (1988) offered specific reliability information about the instrument used, and provided a clear explanation of Speakman and Hoffman's (1979) false score notion as it related to his procedure of telling all subjects about the study ahead of time. Stewart also clearly defined the research question, procedures, and data analysis utilized, including significance testing.…”
Section: Summary Of Nonintervention Studiesmentioning
confidence: 99%
“…Because the persons, in their attempt to formulate a performance that leads to pleasant and commonly accepted answers, may eventually present "fake" answers to make an impression. The specific form of the questionnaire has been tested for the degree of fakeability of the answers and it has been found that the scale is an authentic psychometric mean of measuring the attitudes of people towards disability (Speakman & Hoffmann, 1979).…”
Section: The Research a Samplementioning
confidence: 99%